Eliminating bottlenecks for efficient bioanalysis - Shou, Wilson Z.; Weng, Naidong (Future Science Group, 2014)
Bioanalysis, commonly defined as the quantitative analysis of drugs, metabolites and biomarkers in biological matrices, is an integral part of various activities within the entire drug discovery and development process. With the well-documented declining return on investment of R & D in the pharmaceutical industry, all areas of discovery and development are increasingly being asked to work individually and collectively to increase efficiency and boost productivity in bringing more innovative medicines to the market with flat, or even decreasing, development costs.